Thomas Reid and the problem of secondary qualities - Shrock, Christopher A. (Edinburgh studies in Scottish philosophy., 2017)
With a new reading of Thomas Reid on primary and secondary qualities, Christopher A. Shrock illuminates the Common Sense theory of perception. Shrock follow's Reid's lead in defending common sense philosophy against the problem of secondary qualities, which claims that our perceptions are only experiences in our brains, not of the world.